Analysis Willingness to Pay Goyor Woven Sarong Product in Pemalang - Andriyani, Puput (Efficient: Indonesian Journal of Development Economics, 2020)
Goyor woven sarong is one of the handicrafts weaving in the form of a sarong made using weaving tools instead of machine (ATBM). The purpose of this study is to identify the characteristics of consumers of goyor weaving products, measure the maximum price that consumers are willing to pay, and analyze the factors that affect Willingness to Pay (WTP) of the consumers. This type of research uses a quantitative approach. The data of this study used primary data with 50 respondents, where respondents were consumers of Batik Daffa Shop. Data sources were obtained from distributing questionnaires. The analysis used is descriptive analysis, Contingent Value Method (CVM) approach, and multiple regression analysis. Based on research conclusions, differences in consumer characteristics make the value of Willingness to Pay obtained by each respondent very varied towards the purchase of goyor woven gloves at the Batik Shop Daffa Pemalang, The price consumers are willing to pay for goyor woven gloves Rp. 269,400.00, and the factors that influence the Willingness to Pay goyor woven gloves are variables of product quality and lifestyle. Sarung tenun goyor adalah salah satu kerajinan tenun berupa sarung yang dibuat dengan menggunakan alat tenun bukan mesin (ATBM). Tujuan dari penelitian ini adalah untuk mengidentifikasi karakteristik konsumen produk tenun goyor, mengukur harga maksimum yang bersedia dibayar konsumen, dan menganalisis faktor-faktor yang mempengaruhi Willingness to Pay (WTP) konsumen. Jenis penelitian ini menggunakan pendekatan kuantitatif. Data penelitian ini menggunakan data primer dengan jumlah 50 responden, dimana responden adalah konsumen Toko Batik Daffa. Sumber data diperoleh dari penyebaran kuesioner. Analisis yang digunakan adalah analisis deskriptif, pendekatan Contingent Value Method (CVM), dan analisis regresi berganda. Berdasarkan kesimpulan penelitian, perbedaan karakteristik konsumen menjadikan nilai Willingness to Pay yang diperoleh setiap responden sangat bervariasi terhadap pembelian sarung tangan tenun goyor di Toko Batik Daffa Pemalang, Harga yang bersedia dibayar konsumen untuk sarung tangan tenun goyor Rp. 269.400,00, dan faktor-faktor yang mempengaruhi Kesediaan Bayar Sarung Tangan Goyor adalah variabel kualitas produk dan gaya hidup.